INTELLIGENT ONLINE MONITORING SYSTEMS FOR HIGH-REVOLUTION ROTARY FURNACES - Zelko, Miroslav; Sindler, Vratislav (European Scientific Journal, ESJ, 2013)
This paper characterizes the important features of intelligent monitoring systems and demonstrates how it is transforming mining or raw materials sectors. It reviews and identifies research areas that need to be investigated further, such as adaptation, data fusion and tracking methods in a cooperative multi-sensor environment, extension of techniques to classify complex activities and interactions between detected objects. The growing demand for production variability and safety or security has led to more research in building more efficient intelligent monitoring systems. Therefore, a future challenge is to develop a wide-area distributed multi-sensor monitoring system which has robust, real-time information algorithms able to perform with minimal manual reconfiguration on variable applications. Such systems should be adaptable enough to adjust automatically and cope with changes in the environment like production parameters change, aggregate geometry or aggregate activity.